Bio‐electrochemical evaluation of two‐stage constructed wetland microbial fuel cells with high strength raw domestic wastewater and simultaneous energy recovery. (10th May 2021) - Thakur, Somil; Das, Bhaskar
Abstract: In the present study, two‐stage constructed wetland microbial fuel cell (CW‐MFC) systems were investigated for the treatment of raw domestic wastewater and bioelectricity generation under continuous regime and high organic loading in the presence and absence of Canna indica plant species. Results showed that two‐stage reactors with and without plant produced maximum cell voltage of 0.39, 0.59 V, and 0.27, 0.47 V respectively under OLR of 1.2–3.2 kgCOD/m 3/ d while maximum NERs obtained by systems were 6.85, 4.10, 5.24, 2.28 Wh/kgCOD. Moreover, the highest COD removal efficiencies of 82.29% and 55.72% were achieved for system with plant and without plant respectively. Overall, two‐stage systems showed enhanced utilization of wastewater biomass in to bioelectricity and better pollution removal with Canna indica plant. This work is particularly significant in most of the developing countries where the untreated sewage is of similar COD and TSS range.